ELTD1 is present in extracellular vesicles derived from endothelial cells as a cleaved extracellular domain which induces in vivo angiogenesis. Issue 8 (2nd August 2022) - Sheldon, Helen; Zhang, Wei; Bridges, Esther; Ang, Koon Hwee; Lin, Salwa; Masiero, Massimo; Li, Demin; Handford, Penny A.; Whiteman, Pat; Fischer, Roman; Buffa, Francesca; Vatish, Manu; et al.
Abstract: ELTD1/ADGRL4 is an adhesion GPCR with an important role in angiogenesis. We recently identified a role for ELTD1 in wound repair and inflammation. Activation of ELTD1 in endothelial cells results in a type II EMT to myofibroblast‐like cells that have enhanced angiogenic ability. Furthermore, expression of Eltd1 in murine breast cancer cells increases tumour growth by increasing blood vessel size and perfusion and by creating an immunosuppressive microenvironment. As extracellular vesicles (EVs) are known to be involved in vascular development, growth and maturation we investigated the composition and functional effects of the EVs isolated from ELTD1 expressing cells to elucidate their role in these processes. A highly glycosylated form of the extracellular domain (ECD) of ELTD1 is readily incorporated into EVs. Using mass spectrometry‐based proteomics we identified proteins that are enriched in ELTD1‐EVs and are involved in haemostasis and immune responses. ELTD1 enriched EVs were pro‐angiogenic in vivo and in vitro and the presence of the ECD alone induced endothelial sprouting. In endothelial cells experiencing laminar flow, ELTD1 levels were reduced in the EVs when they are quiescent, showing a relationship between ELTD1 and the activation state of the endothelium. Using FACS, we detected a significant increase in vesicular ELTD1 in the plasma of patients with preeclampsia, a condition characterized by endothelial dysfunction. These data confirm a role for ELTD1 in wound repair and inflammation and reveal its potential as a biomarker of vessel dysfunction.